Analysis of crack response on structures due to blasting and non-blasting factors - Vojinović I.; Stojadinović S.; Svrkota I.; Stojanović M.; Šabaz D. (Journal of Mining and Metallurgy. Section A: Mining)
Seismic waves caused by blasting activities can be a source of damage to structures. The most common damage is the appearance of cracks or the widening of existing cracks. Structures are also affected by environmental factors. Depending on the conditions, temperature and humidity can cause a stronger reaction in the cracks than blasting. However, the effects of non-blasting factors last much longer than those of blasting, so the load gradually increases, allowing for an even and timely distribution of stress around the crack tip. On the other hand, blasting factors act over a short period of time, resulting in a rapid increase in the stress intensity factor at the crack tip and a faster release of stress energy. The FEM (finite element method) analysis of these impacts was conducted on a model in the ABAQUS CAE software. The results of the analysis show that the influence of blasting factors is significantly higher compared to the influence of non-blasting (environmental) factors. The strain energy and the stress intensity factor per unit time are much higher under the influence of blasting factors. The strain energy is 9.58 × 1010 times higher, and the stress intensity factor at the crack tip is 309583 times higher due to the dynamic load, observed over a period of 0.033 seconds.